ANALISIS FIQH MUAMALAH TERHADAP PRAKTIK PEMBATALAN SEPIHAK OLEH KONSUMEN LAYANAN JASA GRABFOOD CABANG MATARAM - Nia Kartika; Saprudin; Ahmad Nurjihadi (Universitas Islam Negeri Mataram, 2021)
Consumers or users in this study are people who use services through the Grab application, either in the form of ordering food or ordering car or motorbike drivers. The use of the Grab application as explained by the informant interviewed by the researcher, according to him, is very easy and practical, but when making an order, it does not rule out the possibility of errors in ordering, either from the inaccuracy of Google Maps providing location access or the most common experience is regarding the cancellation of the purchase because the product is out of stock or not resold. This has resulted in some users not continuing the order or preferring to cancel.